Effects of Life Kinetic and Brain Gym Training Models On Working Memory and Concentration of Football Athletes - Wisnu Murti Ansyah; K Komarudin (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to find out the effect of Life Kinetic and Brain Gym training models on working memory and concentration of junior football athletes and to examine the more effective training model, the Life Kinetic or Brain Gym training models, to improve working memory and concentration of junior football athletes. In this study, the researcher used a quantitative research using the true experiment and the pre-test and post-test two treatment design. The population of this study were all students of Saswco Bandung U-13 Football School, totalling of 26 people. The samples were selected using total sampling technique. Respondents were given the Life Kinetic and Brain Gym training models 3 times a week, carried out for 4 weeks. The instrument for measuring working memory was The Digit Memory Test, while the instrument for measuring concentration was The Amazing 1 to 50. The hypothesis testing analysis technique used was the Multivariate test. The results of the research for the Life Kinetic and Brain Gym training models on working memory and concentration was sig. 0.000 0.05, while the between-subjects effect test value was Sig. 0.000 0.05. It shows that there was a difference between Life Kinetic and Brain Gym training on working memory and concentration of junior football athletes. In conclusion, the Life Kinetic and Brain Gym training models can improve working memory and concentration of junior football athletes. Life Kinetic training had a better effect than Brain Gym training on working memory and concentration of junior football athletes. It is suggested that further research should recall information more specifically during matches and practices of football games by simplifying Life Kinetic and Brain Gym Exercises.